2016
DOI: 10.1002/smll.201503712
|View full text |Cite
|
Sign up to set email alerts
|

Combined Optical and Chemical Control of a Microsized Photofueled Janus Particle

Abstract: A Au-silica Janus particle is elevated along the laser beam axis in an optical trap. The propulsion mechanism is based on the local temperature gradient created around the particle due to the photothermal conversion of the gold-coated hemisphere. The height of the particle and its motion-direction are tuned by the nature and the concentration of the electrolytes in the medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 28 publications
5
41
1
Order By: Relevance
“…Regarding specific-ion effects, our findings agree qualitatively with a recent experiment on gold-capped silica particles, showing a significant variation of the self-propulsion velocity with the used salts NaOH, NaCl, LiCl [9]. The data do not provide conclusive evidence for thermoelectric driving along the metal cap.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Regarding specific-ion effects, our findings agree qualitatively with a recent experiment on gold-capped silica particles, showing a significant variation of the self-propulsion velocity with the used salts NaOH, NaCl, LiCl [9]. The data do not provide conclusive evidence for thermoelectric driving along the metal cap.…”
Section: Discussionsupporting
confidence: 78%
“…Since the thermophoretic self-propulsion is superposed on motion due to radiation pressure and gravity, these data do not provide an absolute measure of v s , but only qualitative differences upon changing the ions. In summary, the data of [9] confirm the existence of an electrolyte Seebeck effect for active > . The left panel shows the case of single grain.…”
Section: Comparison With Experimentssupporting
confidence: 60%
See 1 more Smart Citation
“…The decrease of velocity is owing to the increasing viscosity 33 . On the other hand, salts or proteins in close proximity to the AuNPs clusters could absorb thermal energy, resulting in lower velocity in complex media 47 . Note that the AuNPs-functionalized silica torpedo displays red fluorescence from AuNPs upon the irradiation of NIR laser owing to the surface plasmon resonance as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that, in addition to thermo-osmosis [11,12], the electrolyte Seebeck field [13][14][15][16][17][18] and concentration gradients of salt [16] or nonionic polymers [19,20], play an important role. These companion fields arise from specific solvation enthalpies of salt ions or nonionic solutes, and are at the origin of the "inverse" Soret effect, where the colloids accumulate in hot regions [16,19].…”
mentioning
confidence: 99%